EFFECT OF ASSET TANGIBILITY ON CASH HOLDINGS WITH GROWTH OPPORTUNITY AS MODERATE VARIABLE: (EMPIRICAL STUDY ON PROPERTY AND REAL ESTATE COMPANIES LISTED ON INDONESIA STOCK EXCHANGE) - Nuriyatul Hidayah; Tri Lestari; Windu Mulyasari (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2021)
This study aims to determine the effect of asset tangibility on cash holdings and the effect of growth opportunity on the relationship between asset tangibility to cash holdings. The population in this study are property and real estate companies listed on the Indonesia Stock Exchange during the period 2015-2018. Using the purposive sampling method, 37 companies were complying with criteria as samples. This study used secondary data from the Indonesia Stock Exchange website. Using IBM SPSS 23 data processing application, Moderated regression analysis (MRA) was used as an analytical method. This study indicates that: (1) Asset tangibility has a significant negative effect on cash holdings. It showed by the value of regression coefficient β1 is  -0,00002771 with a significance level (ρ-value) of 0,001 where the value is below the significance level of 0,05 (0,001 <0,05). (2) Growth opportunity as a moderating cannot moderate the effect of asset tangibility on cash holdings. The level of significance (ρ-value) of the growth opportunity and MRA variables, which are 0,206 and 0,823, where the value is more than  0,05 significance level.